Contrast induced acute kidney injury in acute coronary syndrome patients: A single centre experience. Issue 1 (1st February 2016) - Farhan, Serdar; Vogel, Birgit; Tentzeris, Ioannis; Jarai, Rudolf; Freynhofer, Matthias Karl; Smetana, Peter; Egger, Florian; Kautzky-Willer, Alexandra; Huber, Kurt
Abstract: Background: The aim of the study was to investigate predictors of contrast induced acute kidney injury, in-hospital and long-term mortality in patients with acute coronary syndrome treated by percutaneous coronary intervention. Methods: We investigated 536 consecutive patients with acute coronary syndrome who underwent percutaneous coronary intervention. Contrast induced acute kidney injury was classified according to risk, injury, failure, loss of kidney function and end-stage kidney disease/acute kidney injury network (RIFLE/AKIN) criteria into those with normal kidney function, risk, RIFLE stage I and those with stage ⩾II. We investigated in-hospital, all-cause mortality during index hospitalization and long-term all-cause mortality during the follow-up period of 94 months (interquartile 81.6–108.9 months) in adjustment with parameters of the Global Risk of Acute Coronary Events score. Results: Patients with contrast induced acute kidney injury had worse baseline clinical characteristics and displayed more co-morbidities than patients with normal kidney function. In multivariate logistic regression analysis intra-aortic balloon pump use, congestive heart failure, age >75 years and admission serum creatinine >1.5mg/dl were independent predictors of contrast induced acute kidney injury development. contrast induced acute kidney injury RIFLE stage ⩾II was an independent predictor of in-hospital mortality (odds ratio 33.16, confidence interval 1.426–770.79, p =0.029) and long-term mortality (hazard ratio 4.713, confidence interval 1.53–14.51, p =0.007) even after adjustment for confounders (variables of Global Risk of Acute Coronary Events score). Conclusion: Contrast induced acute kidney injury is a common complication of acute coronary syndrome patients treated by percutaneous coronary intervention. Advanced deterioration in renal function after percutaneous coronary intervention is an independent predictor for in-hospital and long-term mortality.